Rephotography for photographers: discussing methodological compromises by post-graduate online learners of photography. Issue 1 (3rd April 2019) - McLeod, Gary
Abstract: Rephotography involves making one or more pictures of the same subject in order to repeat an existing image, usually to show change. Recognized early on as a rigorous visual method for natural sciences, rephotography in popular culture has grown into a popular visual strategy of displaying images of the past within or alongside images of the present, but such images cannot alone explain events that led to their production. While any methodological compromises in scientific applications are usually held to account, the act of rephotographing – as a common and varied set of practices within visual culture – faces far less scrutiny. Focusing on the presence of rephotography in photography education, this paper reports on responses to an explicit rephotographic task given to students of an online MA Photography program and considers compromises regarding two aspects seen as methodologically fundamental: the accuracy applied in revisiting a previously made image and the depth of exploration undertaken in response to it. In doing so, it supports the notion that rephotograph ing as a way of learning through looking at and making images is vital for the visual literacy of photography students.